Penguasaan Konsep Matematika Awal Melalui Media Wayang Angka Kontekstual pada TK A - Widayati Widayati (PG-PAUD Trunojoyo, 2016)
Research in kindergarten Mardi Putra 03 in Group A against the background of the low level of achievement of development, in particular the scope of cognitive development in this regard is devoted to mastering early math concepts. The results of daily and weekly assessment conducted by the teacher can be seen that of the 15 children, only 5 children achieve mastery learning standards prescribed by the teacher but the rest were below average. It is caused by many factors, some teachers still follow the conventional learning and dictatorial in which the child should perform the learning activities while playing but the teacher limited the movement of children. Teachers are less innovative in creating meaningful learning activities in children due to the use of media student worksheet (LKS) as the only medium of learning used by teachers in introducing math concepts early in children. This research method using action research methods (Action Research). This study refers to the research design Kurt Lewin. The subjects were students in group A with the number of 15 children. The results of the study can be seen in the increase in learning outcomes yairu prasiklus children's learning outcomes percentage stood at 23.33%, then the cycle of the study occurred a significant increase is 72.86% and in cycle two an increase of 89.97%.